2021
DOI: 10.3390/ijms22052277
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Particle-Induced Lysosomal Membrane Hyperpolarization to Lysosomal Membrane Permeabilization

Abstract: Lysosomal membrane permeabilization (LMP) has been proposed to precede nanoparticle-induced macrophage injury and NLRP3 inflammasome activation; however, the underlying mechanism(s) of LMP is unknown. We propose that nanoparticle-induced lysosomal hyperpolarization triggers LMP. In this study, a rapid non-invasive method was used to measure changes in lysosomal membrane potential of murine alveolar macrophages (AM) in response to a series of nanoparticles (ZnO, TiO2, and CeO2). Crystalline SiO2 (micron-sized) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“… 23 , 112 Precedent toxicological studies have demonstrated that NPs could break the cell cycle by inducing not only the most common membrane depolarization 23 , 113 but also hyperpolarization. 114 , 115 The fact that cationic NPs are usually more toxic to cells than anionic ones 1 , 15 , 116 , 117 could be tentatively explained in terms of our findings. We have shown that PS-NH 2 has the most potent capacity of membrane disruption, pointing all our findings to membrane depolarization by different mechanisms.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“… 23 , 112 Precedent toxicological studies have demonstrated that NPs could break the cell cycle by inducing not only the most common membrane depolarization 23 , 113 but also hyperpolarization. 114 , 115 The fact that cationic NPs are usually more toxic to cells than anionic ones 1 , 15 , 116 , 117 could be tentatively explained in terms of our findings. We have shown that PS-NH 2 has the most potent capacity of membrane disruption, pointing all our findings to membrane depolarization by different mechanisms.…”
Section: Discussionsupporting
confidence: 66%
“…As regard to NP-induced toxicity, the selective hydrophilic pores created by PS NPs point to a more complex modulation of transmembrane electric potential as summarized in the cartoon of Figure . Cell membranes are characterized by a net negative charge on the cytosolic side of the membrane (usually −40 to −70 mV) that changes during cell proliferation and differentiation. , Precedent toxicological studies have demonstrated that NPs could break the cell cycle by inducing not only the most common membrane depolarization , but also hyperpolarization. , The fact that cationic NPs are usually more toxic to cells than anionic ones ,,, could be tentatively explained in terms of our findings. We have shown that PS-NH 2 has the most potent capacity of membrane disruption, pointing all our findings to membrane depolarization by different mechanisms.…”
Section: Discussionsupporting
confidence: 61%
“…IL-1β levels were reduced in bronchoalveolar lavage (BAL) fluids from animals previously treated with nanoparticles and treated in vitro with C. phaeocaulis . C. phaeocaulis has an anti-inflammatory effect against lung disease associated with excessive activation of the NLRP3 inflammasome/inflammation [ 61 , 62 ].…”
Section: Curcumin Inflammasome and Lungmentioning
confidence: 99%
“…If the process described above occurs in antigen-presenting cells (macrophages or dendritic cells), microorganisms can be processed within the vesicles and generate peptides to be presented in the class II context, thereby initiating a strong antibody response. Then, upon vesicle rupture, microorganism components can be released into the cytoplasm, favoring their presentation in the context of class I molecules and generating cytotoxic T cell responses [ 114 , 115 ]. Thus, the presence of MPs may actually broaden the breadth of specific adaptive immunity against microorganisms by promoting both class II- and class I-dependent specific immunity.…”
Section: Discussionmentioning
confidence: 99%